Recursos humanos estáticos en la modernidad liquida - Julio Alfonso González-Mendoza; Laudy Camila Rodríguez-Rodríguez; Nelson Emilio García-Torres (Mundo Fesc)
Being agile is of paramount importance for a modern organization to remain in the market. Being flexible allows it to anticipate and respond to the opportunities and threats it may face in the face of changes in the complexity of its environment. New societal demands require resources to adapt rapidly to new realities, although it has been found that the management, administration, and handling of Human Resources are still carried out as in the times of Taylor and Fayol and have not evolved at the same pace as other organizational areas. The research objective is to reflect on the evolution of human resources administration and management in organizations, given their importance, and on the evolution and adaptation that has occurred or may occur in a rapidly changing world that Bauman calls liquid modernity. The main conclusions refer to the fact that Human Resources (HR) in organizations have become bureaucratic, dysfunctional, and inflexible, not only not contributing to the organization but also generating tensions among employees. HR administration ends up being hated by staff, as it always seems to be on the side of the company rather than the employee; There is a feeling that every small mistake is exploited to embroil them in problems; although management attempts to reach out and engage with employees, they are often unreliable; abusive behavior from managers is often ignored; the head of human resources is often a specialist in the area who has little understanding of the company's mission or the activities of other team members. Sometimes decisions are made that pit employees against employers, instead of attempting to reconcile and find solutions that benefit all parties.